Ora et Labora Barth's Forgotten Hermeneutical Principle - Gignilliat, Mark S. 1976- (2009)
This article explores the interface between our theological confession, spiritual formation and intellectual efforts in the context of theological exegesis and theological education. In the broader discourse about theological exegesis and methods attendant to these concerns, a central task in the process of reading and interpreting Scripture has not received the attention it deserves and demands. This task, or posture, is prayer. The bulk of the article is given to listening to Karl Barth's formulations of this matter in Church Dogmatics 1.2. For Barth, all of one's theological exegetical labours from beginning to end must take place in the context of prayer.
Keywords: Barth, Karl, 1886-1968; Bible; Bible -- Commentaries; Hermeneutics; Karl Barth; Prayer; Religious Education; Scripture; Theologians; Theological Education; Theological Exegesis